Math, asked by angadsinghkotputli, 1 year ago

if one of the zeros of the quadratic polynomial (k-1)x²+kx+1 is -3 then the value of k will be?

Answers

Answered by Anonymous
47
 \huge \boxed{ \mathbb{ANSWER:}}

 <b> <I> <H3>

 <u> GIVEN:-) </u>

→ One zeros of quadratic polynomial = -3.

→ Quadratic polynomial = ( k - 1 )x² + kx + 1.

 <marquee> <u> Solution:- </u> </marquee>

→ P(x) = ( k -1 )x² + kx + 1 = 0.

→ p(-3) = ( k - 1 )(-3)² + k(-3) + 1 = 0.

=> ( k - 1 ) × 9 -3k + 1 = 0.

=> 9k - 9 -3k + 1 = 0.

=> 6k - 8 = 0.

=> 6k = 8.

 \large \boxed{=> k = \frac{8}{6} = \frac{4}{3} }

 &lt;marquee&gt; &lt;u&gt; ✔✔Hence, the value of ‘k’ is founded . <br />&lt;HR&gt;

 &lt;/H2&gt; &lt;/b&gt; &lt;/u&gt; &lt;/I&gt; &lt;/marquee&gt;

 \huge \boxed{ \mathbb{THANKS}}

 \huge \bf{ \# \mathbb{B}e \mathbb{B}rainly.}
Answered by Anonymous
7

Step-by-step explanation:

GIVEN:-)

→ One zeros of quadratic polynomial = -3.

→ Quadratic polynomial = ( k - 1 )x² + kx + 1.

Solution:- ---

→ P(x) = ( k -1 )x² + kx + 1 = 0.

→ p(-3) = ( k - 1 )(-3)² + k(-3) + 1 = 0.

=> ( k - 1 ) × 9 -3k + 1 = 0.

=> 9k - 9 -3k + 1 = 0.

=> 6k - 8 = 0.

=> 6k = 8.

 \large \boxed{=&gt; k = \frac{8}{6} = \frac{4}{3} }

Hence, the value of ‘k’ is founded .

Similar questions